Evaluation of the uncertainty due to dynamic effects in linear measuring devices - Giovanni Battista Rossi; Francesco Crenna; Marta Berardengo (Measurement: Sensors, 2022)
The evaluation of the uncertainty due to systematic dynamic effects is addressed. When high dynamic performance is required, they should be compensated, by solving the associated inverse dynamic problem. When instead they are considered compatible with the target uncertainty, they may be simply included in the uncertainty budget. Furthermore, even in the case of dynamic compensation, a residual uncertainty remains, due to the imperfect compensation, and should be evaluated. Therefore, simple formulas are presented here, applicable to many classes of dynamic phenomena, including periodic, harmonic, transitory impulsive and stochastic stationary ones.